Effect of perturbation amplitudes on water film stiffness coefficients of water-lubricated plain journal bearings based on CFD–FSI methods. (July 2019) - Liang, Xingxin; Yan, Xinping; Liu, Zhenglin; Ouyang, Wu
A numerical three-dimensional computational fluid dynamics-fluid structure interaction (CFD-FSI) model including lining deformation and cavitation is developed to evaluate the effect of perturbation amplitudes on stiffness coefficients of hydrodynamic water-lubricated plain journal bearings. Three types of bearing with rubber, polymer and steel lining materials are compared in terms of stiffness coefficients, load-carrying capacity and journal center equilibrium position under different eccentricity ( ɛ ) conditions. The simulation results indicate that perturbation amplitudes have great influence on the four stiffness coefficients of water film of hard lining bearings at large ɛ . However, when ɛ ≤ 0.5 and the perturbation varies within 2.9% of the bearing radial clearance, the effect is less than 10% regardless the lining materials. For the rubber lining bearing, the effect of perturbation amplitudes on the stiffness coefficients is negligible due to the rubber deformation, even at ɛ = 1.9 and the perturbation amplitudes up to 7% of the radial clearance. Lining deformation also affects the attitude angle of the journal and the stiffness of water film. The calculation results demonstrate that the lining deformation and journal perturbation amplitudes are two important factors which cannot be ignored in the calculation of bearing stiffness in case of the journal at large eccentricity ratios.